INFLAMMATORY REACTION AGINST MYCOPLASMA GALLISEPTICUM INFECTION IN BROILER - & Ali, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was carried out  to investigate the Inflammatory  reaction in broiler chicken after experimental infection with Mycoplasma gallisepticum(MG) , which were evaluated by using Enzyme Linked Immunosorbent Assay(ELISA) to measure pro inflammatory cytokines and IgG.  one hundred day old  broiler chicks  were randomly divided into five groups 20 birds each group, all groups except group 5 (control) were  infected at two weeks old with 0.2ml of 106  cfu/bird of local MG ,groups treated as follows:  Group1 : infected  Intravenous( I.V) with MG isolate. Group2: : infected  Intraocular (I.O) ,Group3: infected  Intranasal (I.N),Group4: : infected  Intratracheal (I.T) infection, Group5: were not: infected  with MG isolate. Blood samples were collected at 1,2,3and 4 weeks post infection to measure Interleukin 1(IL1),Tummer necrosis factor (TNF),Interferon gamma( IFG) used ELISA, also IgG was measure  ELISA test at 2,3and 4 weeks after infection . The results of Serological test showed the infected groups with MG   revealed significant increase in the  levels of IL-1, IFG, TNF (pro inflammatory cytokines) and IgG production compared with control group ,the group 4( I.T)  had higher  level of these pro-inflammatory cytokines and Immunoglobulins  more than other infected groups in all period post infection. From these result, it was concluded that the local isolate of Mycoplasma gallisepticum  has the ability to  in induce inflammatory reaction in infected broiler chicken.